Mitochondrial NAD+ controls nuclear ARTD1-induced ADP-ribosylation - Hopp, Ann-Katrin; Teloni, Federico; Bisceglie, Lavinia; Gondrand, Corentin; Raith, Fabio; Nowak, Kathrin; Muskalla, Lukas; Howald, Anna; Pedrioli, Patrick G. A.; Johnsson, Kai; Altmeyer, Matthias O.; Pedrioli, Deena M. Leslie; et al. (Molecular cell, 2021)
In addition to its role as an electron transporter, mitochondrial nicotinamide adenine dinucleotide (NAD(+)) is an important co-factor for enzymatic reactions, including ADP-ribosylation. Although mitochondria harbor the most intra-cellular NAD(+), mitochondrial ADP-ribosylation remains poorly understood. Here we provide evidence for mitochondrial ADP-ribosylation, which was identified using various methodologies including immunofluorescence, western blot, and mass spectrometry. We show that mitochondrial ADP-ribosylation reversibly increases in response to respiratory chain inhibition. Conversely, H2O2-induced oxidative stress reciprocally induces nuclear and reduces mitochondrial ADP-ribosylation. Elevated mitochondrial ADP-ribosylation, in turn, dampens H2O2-triggered nuclear ADP-ribosylation and increases MMS-induced ARTD1 chromatin retention. Interestingly, co-treatment of cells with the mitochondrial uncoupler FCCP decreases PARP inhibitor efficacy. Together, our results suggest that mitochondrial ADP-ribosylation is a dynamic cellular process that impacts nuclear ADP-ribosylation and provide evidence for a NAD(+)-mediated mitochondrial-nuclear crosstalk.